Relationship of vegetable and fruit consumption with farmers' blood sugar levels in Pakusari Health Center, Jember - Ayu Pricilia Fatimah; Tantut Susanto; Latifa Aini Susumaningrum; Mokhlas Kholidi (Journal of Community Empowerment for Health, 2022)
Low consumption of vegetables and fruits are one of the causes of digestive problems, coronary heart disease, and diabetes. Farmers are a vulnerable group for consuming vegetables and fruit less than the recommended 5 portions (250 grams) a day. The aim of this study was to analyze the relationship between vegetable and fruit consumption and the level of blood sugar among farmers with non-communicable diseases in the integrated health post (Posbindu) of Pakusari Health Center, Jember Regency. A retrospective cohort study design was used to analyze secondary data of Posbindu registered patients from January to March 2020 among 140 farmers. The characteristics of participants, vegetable and fruit consumption, and blood sugar were measured through the monitoring card of Posbindu. The data were analyzed using Chi-square tests (p-value <0.05). Among 140 farmers as many as 71.4% were identified who consumed vegetables and fruit less than 5 portions a day and 35.7% who have hyperglycemia. There was a relationship between vegetable and fruit consumption and the farmer's blood sugar level (p-value: <0.001; χ2: 13.144). Farmers who consumed vegetables and fruits less than 5 portions a day were 5 times more likely to experience hyperglycemia (RR:5.727; 95% CI=2.072–15.827). Therefore, community health nurses and health care providers should provide counseling to improve the consumption of vegetables and fruits to prevent the incidence of hyperglycemia among farmers.